Mediating CO2 Electroreduction Activity and Selectivity over Atomically Precise Copper Clusters. Issue 35 (14th July 2022) - Liu, Li‐Juan; Wang, Zhi‐Yuan; Wang, Zhao‐Yang; Wang, Rui; Zang, Shuang‐Quan; Mak, Thomas C. W.
Abstract: Atomically precise copper clusters are highly desirable catalysts for electrocatalytic CO2 reduction reaction (CO2 RR) and provide an ideal platform for elaborating structure–activity relationships. However, systematic comparative studies of Cu cluster isomers for electrocatalytic CO2 RR are lacking because they are challenging to synthesize. A group of structurally precise Cu8 cluster isomers with different core structures (cube‐ and ditetrahedron‐shaped) were developed and investigated for highly active and selective CO2 reduction. Electrocatalytic measurements showed that the ditetrahedron‐shaped Cu8 cluster exhibited a higher FEHCOOH (≈92 %) at −1.0 V and higher selectivity than the cube‐shaped cluster. Theoretical investigations revealed different levels of competitiveness with the hydrogen evolution reaction on the respective core‐shaped Cu8 clusters and decreased free energies for the adsorbed HCOO* intermediates on the ditetrahedron‐shaped Cu8 clusters. Abstract : A group of atomically precise Cu8 cluster isomers with two core structures (cube‐ and ditetrahedron‐shaped) were investigated for highly active and selective CO2 reduction. A difference in catalytic performance was attributed to variable metal core arrangements hidden in Cu8 nanoclusters. The ditetrahedron‐shaped cluster exhibits a high Faradaic efficiency for formic acid generation (FEHCOOH ) almost two times that of the cube‐shaped cluster.